Appropriate Complementary Feeding as a Preventive Factor for Growth Faltering in Early Childhood - Pradigdo , Siti Fatimah; Lisnawati, Naintina; Ratnawati, Ratnawati (Bangladesh Journal of Medical Science, 2025)
Background Growth failure in the First 1,000 days of life can affect nutritional and health problems in the next life cycle. Objectives: This study aims to analyze the risk factors for growth failure in children under two years of age based on maternal and child factors. Method and Material This study is an observational study with a case-control design. The subjects of the study were children aged 0-23 months in the working area of the Rowosari Health Center, Semarang City. Cases are children who experience weight gain for 2 months <5 percentile, while controls are children whose weight gain is in accordance with WHO standards. Cases and controls have complete Maternal and Child Health Book, low to middle socio-economic status, no twins, no physical abnormalities, and only one toddler in the family. A sample of 25 children (1:1), selected non probability sampling . The instruments used were digital scales, infantometers, and Child Health Book. The statistical tests used were chi-square and multiple logistic regression. Most cases and controls had normal birth weight, early initiation of breastfeeding, colostrum, and exclusive breastfeeding. Results The feeding pattern in children in most cases did not comply with the guidelines. Risk factors associated with child growth faltering are diet with 95% CI (OR=5.762; CI=1.363-24.362; p=0.027) and birth weight (OR=2.563; CI=1.748-3.757; p=0.002). Conclusion Multiple logistic regression test showed that the dominant risk factor for growth failure is dietary practices, after being controlled for birth weight and maternal education factor. BJMS, Vol. 24 No. 03 July’25 Page : 785-791